Plasma Catestatin: A Useful Biomarker for Coronary Collateral Development with Chronic Myocardial Ischemia. - Weixian Xu; Haiyi Yu; Weihong Li; Wei Gao; Lijun Guo; Guisong Wang (PLoS ONE, 2016)
BACKGROUNDS:Catestatin is an endogenous multifunctional neuroendocrinepeptide. Recently, catestatin was discovered as a novel angiogenic cytokine. The study was to investigate the associations between endogenous catestatin and coronary collateral development among the patients with chronic myocardial ischemia. METHODS:Thirty-eight patients with coronary artery chronic total occlusions (CTO) (CTO group) and 38 patients with normal coronary arteries (normal group) were enrolled in the series. Among the patients with CTO, coronary collateral development was graded according to the Rentrop score method. Rentrop score 0-1 collateral development was regarded as poor collateral group and 2-3 collateral development was regarded as good collateral group. Plasma catestatin level and vascular endothelial growth factor (VEGF) were measured by ELISA kits. RESULTS:The plasma catestatin levels in CTO group were significantly higher than that in normal group (1.97±1.01 vs 1.36±0.97ng/ml, p = 0.009). In the CTO group, the patients with good collateral development had significantly higher catestatin and VEGF levels than those with poor collateral development (2.36±0.73 vs 1.61±1.12 ng/ml, p = 0.018; 425.23±140.10 vs 238.48±101.00pg/mL, p<0.001). There is a positive correlation between plasma catestatin levels and Rentrop scores (r = 0.40, p = 0.013) among the patients with CTO. However, there is no correlations between plasma catestatin levels and VEGF (r = -0.06, p = 0.744). In the multiple linear regression models, plasma catestatin level was one of the independent factors of coronary collateral development after adjustment for confounders. CONCLUSIONS:Plasma catestatin was associated with coronary collateral developments. It may be a useful biomarker for coronary collateral development and potential target for therapeutic angiogenesis in patients with CTO.